THE SECOND YEAR STUDENTS’ PERCEPTION OF MIND MAPPING IN LEARNING VOCABULARY - Juwita Crestiani M; Ardhy Supraba; Hermini, Hermini; Muhammad Hasby; Iin Dwi Aristy Putri (Jurnal Vokatif: Pendidikan Bahasa, Kebahasaan, dan Sastra, 2025)
This research deals with the second year students’ perception of mind mapping in learning vocabulary at Palopo Cokroaminoto University. The population of this research was all The Elementary School Teacher Education Study Program in Cokroaminoto Palopo University in academic year 2025. The total number of population was 10 students. The researcher used the purposive sampling. Based on the findings and discussion in the previous chapter, the researcher concludes that the English students give positive perception mind mapping in Palopo Cokroaminoto University. It is supported by students’ answer about mind mapping that “mind mapping is good and appropriate to be used in learning vocabulary.